PKM Pemberdayaan Ekonomi Masyarakat Melalui Home Industry Donat Berbasis Komunitas di Desa Sumberanyar Kecamatan Paiton Probolinggo - Deddy_Junaedi87; Daud Em Paulia; Raudatul Jannah; Erinda Sulistiana; Intan Rahmadhani; Metalis Putri Pratiwi (CV. Akira Java Bulu, 2024)
Abstract: The community economic empowerment program through a community-based donut home industry in Sumberanyar Village, Paiton District, Probolinggo, aims to improve production and marketing skills and support the economic welfare of the community. This program succeeded in improving participants' technical skills in donut making, strengthening marketing strategies, and contributing significantly to increasing participants' income. However, the program also faces several limitations, such as limited access to capital, obstacles to technology adoption, and fluctuations in market demand. The method used in this service is qualitative with a participatory approach which emphasizes the active involvement of the community in the service process. The implications of the success of this program show that community-based economic empowerment can be an effective model for improving local prosperity and has the potential to be replicated in other areas. To overcome existing limitations, additional support is recommended in the form of access to microfinance, advanced technology training, as well as product diversification and expansion of marketing networks. By implementing these recommendations, it is hoped that the program can achieve sustainability and provide a broader and more sustainable impact on the community Keywords: Empowerment; Community Economy; Home Industry